Pemanfaatan Google Slide dalam Pembelajaran Berbasis Student-Centered Learning (SCL) pada Mahasiswa - Dona Fitriawan; Nurfadilah Siregar; Dian Ahmad BS; Endar Sulistyowati (Program Studi Pendidikan Matematika, 2023)
This study aims to observe the learning process as long as students attend lectures and increase their average learning outcomes using the PBL model by utilizing google slides. The type of research used is quanti-tative. The research method used is a quasi-experimental design in the form of a nonequivalent kontrol group design, meaning that the implementation of the study uses two groups of subjects to be designated as the experimental class and the kontrol class. Time and place of research in rooms 3 and 4 of FKIP Tan-jungpura University whose research was carried out on September 14, 2022. The population was 3 regular classes in the mathematics education study program that taught linear programming courses, while the samples were selected for class VA1 as the experimental class and VA2 as the class. kontrol through a ran-dom draw, each of which amounted to 22 students. The results of the research and data analysis, it can be concluded that the use of the Google Slide-based PBL model is effective on student learning outcomes in the fifth semester linear program material for the Mathematics Education Study Program, FKIP Tanjungpura University. With the results of the hypothesis using the t test, it is obtained which means that it is rejected and accepted so that it can be concluded that the average learning outcomes of students using the SCL model using google slides are better than the TCL learning model. There is also a significant difference in this study, namely learning outcomes in the experimental class with an initial average of 51.55% and then increasing to 81.23%. From the use of google slides in the SCL model, it can improve student learning out-comes both after receiving treatment in the form of the learning process that has been carried out.